THE EFFECT OF USING CONTEXTUAL TEACHING AND LEARNING (CTL) METHOD ON STUDENTS’ ACHIEVEMENT IN WRITING RECOUNT TEXT - Putri Masrita Lubis and Willem Saragih (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2012)
This study aims at investigating the effect of using Contextual Teaching and Learning (CTL) Method on Students’ Achievement in Writing Recount Text. This study was conducted by experimental research. The population of this study was the students of the tenth grade of SMA SWASTA SULTAN ISKANDAR MUDA MEDAN. The total number of the population was one hundred sixty students in 6 classes. There were sixty students chosen as the sample by using random sampling technique. The sample was divided into two groups, namely control group and experimental group. The experimental group was taught by using CTL Method and control group was taught without using CTL Method. The instrument for collecting the data was writing test. The data was analyzed by using t-test formula. The result of the analysis shows that t-observed value is higher than t-table (2.34>2.00) at level of significance 0.05 with the degree of freedom 58. It means that the alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Based on the findings of this study, it was found that there is a significant effect of Contextual Teaching and Learning (CTL) Method on students’ achievement in writing recount text. Key words: Writing, gendre, recount text, Contextual Teaching and Learning (CTL)